ANALYSIS OF REPUTATION RISK MANAGEMENT AT PT JASA MARGA (PERSERO) TBK - Dina Yeni Martia; Nina Woelan Soebroto; Kenneth Pinandhito; Budi Prasetya; Mochammad Abdul Kodir (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
The company's reputation is an intangible asset that is very valuable for public companies in the midst of capital market developments. Therefore, the implementation of risk management is needed to mitigate the reputational risk that arises. This study aims to provide an overview of the analysis of reputation risk management at PT Jasa Marga (Persero) Tbk. The results of the discussion analysis can be concluded that in the period 2018 to 2020 PT Jasa Marga has experienced reputational risk and has been responsively handled by reputation risk management. The existing problems tend to be related to negative publicity and misunderstandings with the media regarding news of construction services, toll road operations, as well as the extent to which projects operate and services are successfully implemented. Mitigation efforts in risk management as a whole intersect with increasing clarification, updating information, as well as building a communication network with the media, optimizing the role of the media, and building a media partnership network. The outputs of this research are the results of the Reputation Risk Management Analysis at PT Jasa Marga and scientific articles in national journals/seminar proceedings